2014
DOI: 10.1111/cup.12286
|View full text |Cite
|
Sign up to set email alerts
|

A prostaglandin d‐synthase‐positive mast cell gradient characterizes scalp patterning

Abstract: These data indicate that scalp is spatially programmed via mast cell prostaglandin D-synthase distribution in a manner reminiscent of the pattern seen in androgenetic alopecia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A 1‐cm strip of full‐thickness skin spanning from the side hairline above the ear and extending to the crown of the scalp was removed from five cadavers who were documented to have androgenetic alopecia at autopsy . Sections were then obtained from five adjacent scalp regions ranging from alopecic (superior at scalp vertex) to normally haired (inferior above ear) skin.…”
Section: Methodsmentioning
confidence: 99%
“…A 1‐cm strip of full‐thickness skin spanning from the side hairline above the ear and extending to the crown of the scalp was removed from five cadavers who were documented to have androgenetic alopecia at autopsy . Sections were then obtained from five adjacent scalp regions ranging from alopecic (superior at scalp vertex) to normally haired (inferior above ear) skin.…”
Section: Methodsmentioning
confidence: 99%
“…Current work is now focused on demonstrating that in human follicles, already identified GPR44 inhibitors also can reverse the hair growth inhibition by PGD 2 . Recent work has also confirmed that the hematopoietic type of PGD2 synthase (HPGDS) also correlates with areas of hair loss(37). …”
Section: Brain Type Lipocalin Prostaglandin D2 Synthase (Ptgds) In Agamentioning
confidence: 85%
“…25 In vitro studies have shown that testosterone induces procollagen formation in dermal fibroblasts and stimulates transforming growth factor-beta 1 synthesis by MCs, inhibiting the rate of hair follicle lengthening and inducing apoptosis. 26 Larson et al 27 showed recently that significantly more dermal MCs are immunoreactive for prostaglandin D-synthase in the vertex compared with the lateral aspects of the scalp in biopsies from balding and nonbalding scalp. Prostaglandin D2 is an inhibitor of hair growth in AGA 28 and is currently a molecule of potential research interest.…”
Section: Alopecia Areatamentioning
confidence: 99%
“…19 Several hair loss disorders outlined below have been associated with MCs. [20][21][22][23][24][25][26][27][28][29] Currently, these findings are of scientific value without direct diagnostic application to practice.…”
Section: Giemsa and Toluidine Blue For Mast Cellsmentioning
confidence: 99%